High Speed Circuits for Lightwave Communications - Chung Wang Keh (World Scientific, 1999)
This text is concerned with high speed circuits and presents information on circuit design, measured results, applications, and product development. It covers electronic and opto-electronic circuits for transmission, receiving and cross-point switching.